SynchLink: an iOS app for ISPyB. (1st October 2014) - Ginn, Helen Mary; Mostefaoui, Ghita Kouadri; Levik, Karl Erik; Grimes, Jonathan Mark; Walsh, Martin Austin; Ashton, Alun William; Stuart, David Ian
<x xml:space="preserve">Abstract</x> The macromolecular crystallography (MX) user experience at synchrotron radiation facilities continues to evolve, with the impact of developments in X‐ray detectors, computer hardware and automation methods making it possible for complete data sets to be collected on timescales of tens of seconds. Data can be reduced in a couple of minutes and in favourable cases structures solved and refined shortly after. The information‐rich database ISPyB, automatically populated by data acquisition software, data processing and structure solution pipelines at the Diamond Light Source beamlines, allows users to automatically track MX experiments in real time. In order to improve the synchrotron users' experience, efficient access to the data contained in ISPyB is now provided via an iOS 6.0+ app for iPhones and iPads. This provides users, both local and remote, with a succinct summary of data collection, visualization of diffraction images and crystals, and key metrics for data quality in real time.